Long-term health-related and economic consequences of short-term outcomes in evaluation of perinatal interventions - Teune Margreet J; van Wassenaer Aleid G; Mol Ben Willem J; Opmeer Brent C (BMC, 2010)
Abstract Background Many perinatal interventions are performed to improve long-term neonatal outcome. To evaluate the long-term effect of a perinatal intervention follow-up of the child after discharge from the hospital is necessary because serious sequelae from perinatal complications frequently manifest themselves only after several years. However, long-term follow-up is time-consuming, is not in the awareness of obstetricians, is expensive and falls outside the funding-period of most obstetric studies. Consequently, short-term outcomes are often reported instead of the primary long-term end-point. With this project, we will assess the current state of affairs concerning follow-up after obstetric RCTs and we will develop multivariable prediction models for different long-term health outcomes. Furthermore, we would like to encourage other researchers participating in follow-up studies after large obstetric trials (> 350 women) to inform us about their studies so that we can include their follow-up study in our systematic review. We would invite these researchers also to join our effort and to collaborate with us on the external validation of our prediction models. Methods/Design A systematic review of neonatal follow-up after obstetric studies will be performed. All reviews of the Cochrane Pregnancy and Childbirth group will be assessed for reviews on interventions that aimed to improve neonatal outcome. Reviews on interventions primary looking at other aspects than neonatal outcome such as labour progress will also be included when these interventions can change the outcome of the neonate on the short or long-term. Our review will be limited to RCTs with more than 350 women. Information that will be extracted from these RCTs will address whether, how and for how long follow-up has been performed. However, in many cases long-term follow-up of the infants will not be feasible. An alternative solution to limited follow-up could be to develop prediction models to estimate long-term health outcomes of the newborn based on specific perinatal outcomes and other covariates. For the development of multivariable prediction models for several health outcomes, we will use data available from a Dutch cohort study of preterm (< 32 weeks) and/or small for gestational age infants (< 1500 g). These infants were born in The Netherlands in 1983 and followed until they reached the age of 19. Discussion The systematic review will provide insight in the extent and methods used for follow-up assessments after obstetric RCTs in the past. The prediction models can be used by future studies to extrapolate short-term outcomes to a long-term horizon or to indicate for which neonates long-term follow-up is required, as their outcomes (either absence or presence of sequelae) cannot be adequately predicted from short-term outcomes and clinical background characteristics.